2022
DOI: 10.1371/journal.pgph.0000515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in Nigeria: Systematic review and meta-analysis of population-based studies

Abstract: In Nigeria, several studies have assessed the prevalence of overweight/obesity with different reports. The purpose of this study was to use a systematic review and meta-analysis to analyze these overweight and obesity reports from different locations in Nigeria over the last ten years. In addition, there was a dearth of systematic reviews and meta-analyses on the prevalence, trends, and demographic characteristics of overweight and obesity in the country. This was a systematic review and meta-analysis of cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…52–54 Obesity is also associated with premature death, hypertension, breathing difficulties, increased risk of fractures and other disability in adulthood when present in children. 52,54,55 Findings from our study compare to findings from an RCT assessing the effect of MI on wellness which found a significant improvement in BMI and WC following intervention with MI over 6 months compared to controls. 38 A prospective intervention study that involved the use of MI among hypertensive patients in Sweden over 1 year found a statistically significant improvement in weight, BMI and waist circumference.…”
Section: Discussionsupporting
confidence: 52%
“…52–54 Obesity is also associated with premature death, hypertension, breathing difficulties, increased risk of fractures and other disability in adulthood when present in children. 52,54,55 Findings from our study compare to findings from an RCT assessing the effect of MI on wellness which found a significant improvement in BMI and WC following intervention with MI over 6 months compared to controls. 38 A prospective intervention study that involved the use of MI among hypertensive patients in Sweden over 1 year found a statistically significant improvement in weight, BMI and waist circumference.…”
Section: Discussionsupporting
confidence: 52%
“…An earlier study in Ghana [ 18 ] found women to have a 1.3 times and 3.7 times higher prevalence of overweight and obesity respectively than men with urban dwellers registering a prevalence rates of 10.5% and 12.6% higher for overweight and obesity compared to rural dwellers. In the study conducted in Nigeria [ 38 ], pooled data from studies conducted between 2010 and 2022 was used in a meta- analysis and the prevalence of overweight was higher among women by 2% than men and obesity prevalence among women was 12.1% higher than in men. Ekpor et al [ 39 ] studied overweight and obesity prevalence in the larger Africa region and noted that females were more likely to be overweight and obese compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Marital status Respondent's marital status was categorized and coded into; not married (0) and married (1).…”
Section: Religion This Was Categorized and Coded Into Christian (1) I...mentioning
confidence: 99%
“…The prevalence of overweight/obesity is rapidly increasing in the low-and-middle-income countries (LMIC), particularly in Africa [ 1 , 2 ]. For more than four decades, the prevalence of overweight/obesity among adolescents has been increasing rapidly globally, and more importantly in Africa [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%